Yugoslav Republic of Macedonia : Second Post-Program Monitoring Discussions. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper reviews the key points of Second Post-Program Monitoring Discussions with the Former Yugoslav Republic of Macedonia (FYR Macedonia). Growth in FYR Macedonia continues to strengthen, although the recovery is not yet broad-based. External and fiscal vulnerabilities have risen: private non-debt-creating capital flows have slowed and could leave the reserve path increasingly driven by an accumulation of external public debt. Central government debt has increased by about 15 percentage points since the beginning of the global financial crisis, in the context of growing broader public sector operations. In the absence of domestic spillovers, the structural improvement in the trade deficit will be gradual, and growth could be uneven.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet